Impact of Surface-Mounted Permanent Magnets Imperfections on the Machine - Vícha, Adam (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2016)
Study sums up issues of mounting permanent magnets onto rotor surface of permanent magnet synchronous machine. Fully parametric model of rotor with surface mounted permanent magnet was created. Model was subjected to analysis of offset of permanent magnet, wrong magnetization and manufacturing width tolerance. Fourier transformation was performed with the results to separate the imperfections via cogging torque and induced voltages.
Keywords: magnet imperfections; cogging torque; induced voltage; FEM; synchronous machine